Validity of Improved MTL for Effective Length of Counterpoise Wires under Low and High-Valued Lightning Currents - Ostadzadeh, S. R. (Advanced Electromagnetics, 2020)
In this paper, an efficient modeling approach called improved MTL is used to predict effective length of counterpoise wires considering both ionization and dispersion of soils. This paper consists of two parts. At first part, validity of the model for computing effective length of counterpoise wires considering only soil ionization is investigated. The simulation results show that the improved MTL-based effective length of counterpoise wire are in good agreement with the existing formulae. Application of this modeling approach to include ionization and dispersion effects simultaneously (both-affected soil) is carried out in the second part. The simulation results show that in both-affected soils, the effective length with respect to only-ionized soils, is decreased especially in highly resistive soils under slow-fronted currents. This makes inclusion of both effects financially important in designing counterpoise wires.